The effect of siberian ginseng (eleutherococcus senticosus) on substrate utilization and performance during prolonged cycling - Eschbach, L. C.; Webster, M. J.; Boyd, J. C.; McArthur, P. D.; Evetovich, T. K. (International Journal of Sport Nutrition and Exercise Metabolism, 2000)
It has been suggested that Eleutherococcus senticosus (ES), also known as Siberian ginseng or ciwuija, increases fat utilization in humans. The purpose of this study was to examine the physiological responses to supplementation with ES in endurance cyclists. Using a randomized, double-blind crossover design, 9 highly-trained men (28 ± 2 years, VáO2max 57.3 ± 2.0 ml á kg-1 á min-1) cycled for 120 min at '60% VáO2max followed by a simulated 10-km time trial. Diet was controlled, and ES (1,200 mgá day-1) or a placebo (P) were administered for 7 days prior to each of the two trials. Oxygen consumption, respiratory exchange ratio, and heart rate were recorded every 30 min, and rating of perceived exertion, plasma [lactate], and plasma [glucose] were recorded every 20 min during the 120 min of steady state cycling. There were no significant differences (p > .05) between the ES and P groups at any steady-state time interval or during the cycling time trial (ES = 18.10 ± 0.42, P = 17.83 ± 0.47 min). In contrast with previous reports, the results of this study suggest that ES supplementation does not alter steady-state substrate utilization or 10-km cycling performance time.